How Could You Arrive Late to the Knowledge of Things? On Logos and Ousia in Plato’s Cratylus - Escobar Moncada, Jairo Iván (Estudios de Filosofía, 2006)
I plan to discuss the Theory of Language that Plato expounds in this dialogue. His point of view tries to evade both the dangers of the Naturalist posture of Cratylus and those involved in Hermógenes’ Conventionalist position, even though I believe that Plato ’s position is closer to that of Hermógenes: Language as a social praxis (387c ss.) The horizon which guides his question is the epistemic relation between logos and thing (on. pragma), that is. it enables one to know the Language of Things and the World. The etymological parts of the dialogue show that making a start from the atomic word is a mistake; a detached word of a phrase does not create any connection between the language and the world. We can only know the essence of something or show its essence by means of an entwining of words, since a sentence is the least unity with meaning in language, in which we entwine words, that is, a noun and a verb. Therefore, for my reading, the passage 432dll-433al is important, in which is shown the indispensable character of logos to show what a Thing is. Another question is if the essence can be plainly shown by means of language.